2017
DOI: 10.24818/jamis.2017.04002
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of financial information and contents of the new audit report for lending decisions of commercial banks

Abstract: Abstract:This research study examines the importance of financial information and information contained in the ISA's New Audit Report effective from 2016 for lenders as capital providers. We base our findings on a survey conducted in September of 2016 with corporate loan officers for medium-large corporate clients in Macedonia. The results show that the annual report of the company, except for the management report and notes to the financial statements, has consistently high importance and usability for respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
0
12
0
4
Order By: Relevance
“…Previous archival research exhibited heterogeneous results. Some studies supported the additional information value of KAMs and found that information asymmetry significantly decreased and abnormal trade volume profoundly increased following the implementation of the KAMs disclosures (Almulla and Bradbury, 2018;Reid et al, 2015;Smith, 2017;Trpeska et al, 2017;Porump et al, 2018). Experimental research focuses on the impact of KAMs on individuals' behavior.…”
Section: ⅱ Theory and Hypothesesmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous archival research exhibited heterogeneous results. Some studies supported the additional information value of KAMs and found that information asymmetry significantly decreased and abnormal trade volume profoundly increased following the implementation of the KAMs disclosures (Almulla and Bradbury, 2018;Reid et al, 2015;Smith, 2017;Trpeska et al, 2017;Porump et al, 2018). Experimental research focuses on the impact of KAMs on individuals' behavior.…”
Section: ⅱ Theory and Hypothesesmentioning
confidence: 96%
“…Velte and Issa (2019) reviewed 49 empirical studies on KAMs based on five major streams, including shareholders, debtholders, external auditors, boards of directors, and other stakeholders. Most studies focused on the effect of KAMs on investors' decision and reaction (Christensen et al, 2014;Kachelmeier et al, 2017;Rapley et al, 2018;Almulla and Bradbury, 2018;Trpeska et al, 2017;Porump et al, 2018;Bedard et al, 2018;Gutierrez et al, 2018). Although regulators require auditors to disclose KAMs in the audit report, the adequacy of the description of a KAM is a matter of professional judgment (IAASB, 2015).…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…; Bédard et al,2019;Bava & di Trana,2019; (Bundy,2019Akande et al,2020Casterella et al,2020;Dhaliwal et al,2020;Maffei et al,2020 (Guillamon,2003;Pucheta et al,2004;carcello et al,2009;Omri et al,2011;Kabajeh et al .2012;Feldmann&Read,2013;Christensen et al,,2014;Gyau et al ,2016;Chen Trpeska et al ,2017;Sirois et al, ck, 2016;et (Pucheta et al,2004;carcello et al, 2009;Bhimani et al,2009;Omri et al, 2011;Kabajeh et al, (Noghondari and Foong, 2013;Sormunen,2014;Miazee et al,2014;Mishra& Metilda,2015;Boolaky & Quick,2016;Trpeska et al,2017;Almilia and Wulanditya,2017;Samad,2017;Näsman, 2019 Sig. (2-tailed) .…”
Section: ‫ملخص‬ ‫البحث‬mentioning
confidence: 99%
“…This prior research is not specifically focused on going concern related key audit matters and shows mixed results (e.g. Bé dard, Coram, Espahbodi, & Mock, 2016;Boolaky & Quick, 2016;Bozinovska Lazarevska & Serafimoska Trpeska, 2016;Christensen, Glover, & Wolfe, 2014;Cordoş & Fülöp, 2015b;Evers, Van Buuren, & Van Nieuw Amerongen, 2019;Gold & Heilmann, 2019;Masdor & Shamsuddin, 2018;Sirois, Bé dard, & Bera, 2018;Trpeska, Atanasovski, & Bozinovska Lazarevska, 2017). According to a review study by Masdor and Shamsuddin (2018), going concern issues are not in the top 4 of reported key audit matters.…”
Section: /A26 + or --Yes/nomentioning
confidence: 99%
“…Therefore, we consider the introduction of this heading mainly as a cosmetic adjustment. Based on a survey study, Trpeska, Atanasovski, and Bozinovska Lazarevska (2017) find that loan officers consider information about a material uncertainty related to going concern as highly important, however with a rating similar to the rating given to the emphasis of matter paragraph as included in the previous auditor"s report format.…”
Section: /A26 + or --Yes/nomentioning
confidence: 99%